Exploring Factors Influencing Open Innovation Adoption in SMEs: The Evidence from Emerging Markets - Wilert Puriwat; Suchart Tripopsakul (Ital Publication, 2021)
Open Innovation (OI) is among the vital innovation paradigms for assisting small and medium enterprises (SMEs) to effectively implement innovation initiatives. Drawing on the concepts of organisational agility and absorptive capacity with transaction cost theory, this study’s goal is to investigate factors affecting the adoption of an Open Innovation (OI) orientation in Thai SMEs. Using data from 214 SMEs in Thailand, structural equation modelling validated the model and analysed the proposed hypotheses. The results show that organisational agility, economic and financial readiness and absorptive capacity relate positively to OI adoption and innovation performance. Organisational agility (b = 0.553) had the greatest influence on OI adoption, then economic and financial readiness (b = 0.405) and absorptive capacity (b = 0.387) followed. The results of mediation analysis also reveal that OI adoption partially mediates the effects of organisational agility and absorptive capacity on innovation performance. Our study provides a trailblazing empirical analysis of the major factors influencing SMEs’ OI adoption and performance, extending knowledge of OI adoption by SMEs in emerging economies. The paper proposes a holistic framework for examining SMEs’ OI adoption and performance, through the integration of organisational agility, absorptive capacity and transaction-cost concepts. Doi: 10.28991/esj-2021-01295 Full Text: PDF